The dopamine system, Parkinson's disease and language function. (June 2018) - McNamara, Patrick; Durso, Raymon
Highlights: Dopamine innervates both the frontal parietal and the social brain networks. Language pragmatics depends on frontal parietal and social brain networks PD is associated with deficits in language pragmatics. Abstract : The mesocortical dopaminergic system innervates two major forebrain networks important in language processing: the frontal–parietal network (FPN) and the 'social brain' network. We argue that the FPN may contribute to mediation of grammatical/syntactic aspects of language function while the social brain network may support pragmatic language processes. Patients with Parkinson's disease (PD) evidence deficits in both brain networks and both linguistic domains: on grammatical sentence processing tasks and on pragmatic language tasks. The pragmatic deficits appear to be more pervasive than the syntactic/grammatical deficits, though a theoretical account of these deficits is lacking. While dopaminergic systems likely contribute to modulation of speech acts in patients with PD, there is, as yet, no clear theoretical account of how that is accomplished.